2017
DOI: 10.26630/jk.v8i1.406
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kadar Timbal (Pb) pada Rambut Pekerja Bengkel Tambal Ban dan Ikan Mas di Sepanjang Jalan Soekarno-Hatta Bandar Lampung Secara Spektrofotometri Serapan Atom

Abstract: Analysis of Content (Pb) in Hair Tire Repair Shop Workers and Golden FishAlong The Soekarno-Hatta Bandar Lampung with Atomic Absorption Spectrophotometry. Lead is often referred to as a lead or of lead, the metal is denoted by Pb. Heavy metal lead can cause poisoning and accumulate in the human body. Process of entry into the body can lead through food and drink, the air and the penetration of the skin. Absorption through the skin may occur due to these compounds soluble in oils and fats. Lead through the air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
3
0
4
Order By: Relevance
“…Length of exposure is defined as the exposure time of workers to Pb. However, according to research in Bandar Lampung, the duration of exposure to substances will affect the concentration of Pb entering the body (Samsuar et al, 2017). The same thing was also mentioned in the research in Kampung Rambutan, time/length of work had a significant effect on Pb levels contained in the body where workers with daily working hours of more than 8 hours had Pb levels in Ade Kelana Risfiardy, Novrikasari*, Yuanita Windusari Fakultas Kesehatan Masyarakat Universitas Sriwijaya Corresponding author: *E-mail: novrikasari@fkm.unsri.ac.id the blood that exceeded the threshold (Sofyan, Wintarsih, & Ismail, 2020).…”
Section: The Length Of Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Length of exposure is defined as the exposure time of workers to Pb. However, according to research in Bandar Lampung, the duration of exposure to substances will affect the concentration of Pb entering the body (Samsuar et al, 2017). The same thing was also mentioned in the research in Kampung Rambutan, time/length of work had a significant effect on Pb levels contained in the body where workers with daily working hours of more than 8 hours had Pb levels in Ade Kelana Risfiardy, Novrikasari*, Yuanita Windusari Fakultas Kesehatan Masyarakat Universitas Sriwijaya Corresponding author: *E-mail: novrikasari@fkm.unsri.ac.id the blood that exceeded the threshold (Sofyan, Wintarsih, & Ismail, 2020).…”
Section: The Length Of Workmentioning
confidence: 99%
“…It is possible to detect lead exposure in the body using hair. Several studies in Indonesia have been conducted to determine lead exposure through hair, including research on the Soekarno-Hatta Bandar Lampung road, namely tire patch workers (Samsuar, Kanedi, & Pebrice, 2017). Analysis of lead levels in the hair of city transport drivers in Tamalate District, Makassar City, to be precise on Jalan Andi Pangeran Pettarani, this study showed that in all study samples, lead levels were found to exceed the threshold levels, according to WHO, lead levels in hair were ≤ 12 µg/g (Alimudin & Sulfiani, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Jumlah senyawa timbal lebih besar (62%) dibandingkan senyawa lain, dan timbal tidak mengalami proses pembakaran yang sempurna menyebabkan jumlah timbal yang dibuang ke udara melalui asap buangan kendaraan sangat tinggi (Palar, 2008). Timbal yang terbuang lewat knalpot adalah satu diantara zat pencemar diudara (Samsuar & Pebrice, 2017).…”
Section: Pendahuluanunclassified
“…Paparan timbal sangat dirasakan oleh kelompok masyarakat yang sering dan lama kontak terhadap sumber pencemaran timbal yang disebut sebagai masyarakat resiko tinggi, salah satu pekerjaan yang beresiko terhadap pencemaran timbal adalah pekerja bengkel kendaraan (Samsuar & Pebrice, 2017). Menurut Ramadhani (2018) keracunan timbal (Pb) dapat dialami oleh pekerja bengkel melalui asap kendaraan yang sedang diperbaiki.…”
Section: Pendahuluanunclassified
“…Menurut CDC's kadar timbal normal dalam darah sebesar 10 μg/dL, sedangkan berdasarkan US EPA nilai biological exposure indices (BEIs) Pb dalam darah sebesar 30 μg/dL, dan menurut WHO adalah sebesar 10-25 μg/dL (AOEC, 2013). Samsuar, et al, (2017) melakukan penelitian tentang analisa pb pada pekerja tambal ban di Tambal bandar Lampung, diperoleh kadar Pb rata-rata pada pekerja tambal ban sebesar 9,66 -17,98 µg/dL. Penyebab perbedaan kadar ini adalah tingkat paparan yang dihasilkan, karena Jalan Raya Pantura Kota Pekalongan, merupakan jalan utama menuju Jakarta sehingga tingkat kepadatan lalu lintasnya lebih besar ditambal bandingkan Jalan Soekarno Hatta di Tambal bandar Lampung.…”
Section: Hasil Dan Pembahasanunclassified